Dietary Diversity Using the Minimum Dietary Diversity-Women Indicator in Pregnant Women - Salsabila, Irfia Ainun; Effendy, Devi Savitri (Universitas Mandala Waluya, 2025)
Eating a variety of foods is very important to prevent nutritional deficiencies, especially micronutrients. Low dietary diversity results in vulnerability to nutritional deficiencies. Malnutrition in pregnancy can adversely affect the mother and fetus. This study aims to evaluate the adequacy of dietary diversity and food group consumption patterns of pregnant women in the Lambai Health Centre working area. This type of research is a descriptive study with a cross-sectional design. This study was conducted from November to December 2024 in the working area of Lambai Health Centre, Lambai District, North Kolaka. The sampling technique in this study used total sampling so that the sample size was 47 pregnant women. The level of dietary diversity was evaluated using the Minimum Dietary Diversity for Women (MDD-W) with the criteria of consuming at least five food groups categorized as adequate. The results showed that the majority of pregnant women met the MDD-W criteria (93.6%), and only 6.4% had inadequate dietary diversity. The most consumed food groups were staple foods (100%), namely carbohydrate sources of cereals, tubers, and bananas, meat (95.7%), and green leafy vegetables (93.6%). However, there was no consumption of nuts and seeds. This suggests the need for nutrition education regarding the importance of food variety to support adequate micronutrients during pregnancy.